Pengaruh Pemberian Probiotik Biolacto dengan Dosis yang Berbeda pada Pakan terhadap Pertumbuhan Berat Mutlak Udang Vaname (Lithopenaeus Vannamei) DOC 80 Hari - Prima Farhan Septian; Didik Budiyanto; Sumaryam Sumaryam (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Vannamei shrimp is one of the shrimp species with economic value and is one of the national leading commodities. On the other hand, one of the problems in vannamei shrimp cultivation is its slow growth, slow growth is caused by the less optimal absorption of nutrients in the feed. In dealing with these problems, one of the things that is done is the administration of probiotics. The addition of probiotics such as Biolacto containing Lactobacillus sp bacteria to the feed can increase the appetite of shrimp. This study aims to determine the effect of biolacto probiotics on feed on the growth of the absolute weight of vannamei shrimp. This study used a Complete Random Design (RAL) with four treatments: A (feed without a mixture of probiotics), B (probiotics 2 gr/100 gr feed), C (probiotics 4 gr/100 gr feed), and D (probiotics 6 gr/100 gr feed). Treatment B with a concentration of probiotics 2gr/100g feed gave the highest absolute weight growth of 9.2 gr. Water quality data during the study were obtained with water temperature ranging from 28.5 – 29.2°Celsius, salinity ranging from 36 – 37 ppt, pH ranging from 7.5 – 8.0, and dissolved oxygen ranging from 4.0 to 4.63 mg/l. The results of the ANOVA analysis of the four water quality parameters showed no difference between treatments and were in the optimal range of life of vannamei shrimp (Litopenaeus vannamei).